2021
DOI: 10.3390/ma14247584
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cobalt on the Deformation Behaviour of a Porous TiNi-Based Alloy Obtained by Sintering

Abstract: This research investigates the effect of cobalt on the deformation behaviour of a porous TiNi-based alloy that was obtained by sintering. Porous TiNi-based alloys with cobalt additives, accounting for 0–2 at. % and with a pitch of 0.5, were obtained. The structural-phase state of the porous material was researched by X-ray structural analysis. The effect of different amounts of Co (used as an alloying additive) on the deformation behaviour was investigated by tensile to fracture. The fractograms of fracture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The method used to highlight the austenitic grain is the method of controlled oxidation and is done as follows: A flat face of the sample must be sanded, and the rest must show no signs of oxidation [ 9 , 13 ]; The sample is placed in the oven with the surface sanded up and is kept for 1 h at the austenite temperature provided for each quality of material; then open the oven door and leave the sample in its door for about 10–15 s for oxidation, then place the iron in water; In the case of significant oxidation, the oxide adhering to the polished surface is easily removed by grinding with fine sandpaper, after which the sample is attacked with Villella reagent (1 g picric acid, 5 mL hydrochloric acid, 100 mL ethyl alcohol) [ 14 , 15 , 16 , 17 , 18 , 19 ] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method used to highlight the austenitic grain is the method of controlled oxidation and is done as follows: A flat face of the sample must be sanded, and the rest must show no signs of oxidation [ 9 , 13 ]; The sample is placed in the oven with the surface sanded up and is kept for 1 h at the austenite temperature provided for each quality of material; then open the oven door and leave the sample in its door for about 10–15 s for oxidation, then place the iron in water; In the case of significant oxidation, the oxide adhering to the polished surface is easily removed by grinding with fine sandpaper, after which the sample is attacked with Villella reagent (1 g picric acid, 5 mL hydrochloric acid, 100 mL ethyl alcohol) [ 14 , 15 , 16 , 17 , 18 , 19 ] …”
Section: Methodsmentioning
confidence: 99%
“…In the case of significant oxidation, the oxide adhering to the polished surface is easily removed by grinding with fine sandpaper, after which the sample is attacked with Villella reagent (1 g picric acid, 5 mL hydrochloric acid, 100 mL ethyl alcohol) [ 14 , 15 , 16 , 17 , 18 , 19 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained composite powders were used as raw stock in additive deposition systems. In research work [27], it was shown that the structure of the materials obtained by direct laser deposition inherits the structure of the particles of the SHS powders. Titanium nitride particles are evenly distributed in the intermetallic CrNi matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Nb as a doping element has attracted particular attention due to its effects in enhancing the yield strength through the formation of ultrafine grains, good corrosion resistance at high temperature, and high dislocation density [24][25][26]. Co-addition is also beneficial in improving the solid solution strengthening effect and magnetic hysteresis, thereby improving the thermal coupling performance and oxidation resistance [27]. During the forming process and application, the TiNi alloy will suffer differential strain rate deformation, so it is necessary to investigate the strain rate effect on the TiNi alloy.…”
Section: Introductionmentioning
confidence: 99%